(untitled) (Economic Journal of Nepal, 2018)
This paper analyses the different macroeconomic indicators of three landlocked developing countries to identify the Gulliver effect. Initially, it analyses the trade and economic size of Botswana, Lao PDR, and Nepal corresponding to their respective big neighbour South Africa, Thailand, and India, respectively. The paper further analyses the major macroeconomic indicators of these landlocked developing countries. The findings signal for the existence of the Gulliver effect in trade. Moreover, the paper extends the analysis of the Gulliver effect in inflation, interest rate and exchange rates. The findings support the presence of Gulliver effect. The study found that prime macroeconomic variables of these landlocked developing countries move in a similar direction following almost similar pattern with those of Gulliver neighbours in different magnitudes though.